Assessment of Anaemia among Children Suffering from Severe Acute Malnutrition - Hasan, Ahmed Rashidul; Farhana, Tanzila; Haque, Emdadul; Mahmud, Salahuddin (Dhaka Shishu (Children) Hospital Journal, 2026)
Background: Severe anaemia is a major cause of morbidity, hospitalization, and mortality in children suffering from severe acute malnutrition. Severe acute malnutrition (SAM) with anaemia leads to greater mortality rates compared to SAM without anaemia. Objective: To assess anaemia in children suffering from severe acute malnutrition. Methods: The cross-sectional observational study was conducted at the SAM corner under the Department of Pediatrics, Gastroenterology, Hepatology, and Nutrition of Bangladesh Shishu Hospital & Institute from January 2020 to December 2022. A total of 60 children aged 6 to 59 months with a diagnosis of SAM were included in the study as cases. Another 60 children were enrolled in the study as controls. Controls were taken from children who were in the same age range and socioeconomic background and admitted to the hospital due to causes other than SAM or its complications. The study excluded children with primary hematological diseases. Results: A total of 64 (53.3%) are male and 56 (46.6%) are female. Anemic status: normochromic normocytic 21 (35%) in SAM and 23 (38.3%) in control; normochromic normocytic anaemia 17 (28.33%) in SAM and 28 (46.67%) in control; iron deficiency anaemia 18 (30%) in SAM and 7 (11.6%) in control; and megaloblastic anaemia 4 (6.6%) in SAM and 2 (3.3%) (p < 0.05). A significant relation was found between the mean hematological parameter between SAM and control. Conclusion: This study highlights that anaemia is widespread among malnourished children, with microcytic hypochromic anaemia being the most commonly observed type. It also revealed marked hematological changes, including significant alterations in white blood cell and platelet counts. DS (Child) H J 2024; 40(1): 12-17